Copaiba oil’s bactericidal activity and its effects on health and zootechnical performance for Nile tilapia after oral supplementation - de Mello, Nicoli Paganoti [UNESP]; Carlos Ramos Espinoza, Fernando [UNESP]; da Silva Claudiano, Gustavo; Yunis-Aguinaga, Jefferson; Graça de Oliveira Carvalho, Janaina [UNESP]; Elizabeth Almeida Silva, Josiane; Cristina Pacheco de Oliveira, Elaine; Rodini Engrácia de Moraes, Julieta [UNESP] (Springer Nature, 2024)
Tilapia is one of the most important farmed fish in the world and the most cultivated in Brazil. The increase of this farming favors the appearance of diseases, including bacterial diseases. Therefore, the aim of this study was to evaluate the bactericidal activity of copaiba oil, Copaifera duckei, against Streptococcus agalactiae and Flavobacterium columnare and the dietary effect of copaiba oil on zootechnical performance, hematological, biochemical, immunological, and histological analysis before and after an intraperitoneal infection (body cavity) with S. agalactiae in Nile tilapia. For this, fish were randomly distributed into 15 fiber tanks in five treatments (0, 0.25, 0.50, 0.75, and 1.0%) and fed with a commercial diet supplemented with copaiba oil for 30 days. After this period, the fish were randomly redistributed for the experimental challenge with S. agalactiae into six treatments (T0, T1, T2, T3, T4, and T5), the fish were anesthetized, and blood samples were collected to assess hematological, biochemical, immunological, and histological parameters. Copaiba oil showed bactericidal activity against Streptococcus spp. and Flavobacterium spp. in vitro. In addition, concentrations of 0.75 and 1.0% of copaiba oil have an anti-inflammatory effect and improve hematological and immunological parameters, increasing leukocyte numbers, albumin, and serum lytic activity. Furthermore, there is an increase in the intestinal villus length and tissue damage in groups at concentrations of 0.75 and 1.0% of copaiba oil. In conclusion, copaiba oil presented bactericidal activity against Streptococcus spp. and Flavobacterium spp. in vitro, and oral supplementation at concentrations of 0.75 and 1.0% compared to the control group enhanced non-specific immune parameters and digestibility in Nile Tilapia.
Keywords: Flavobacterium columnare; Immunology; Oreochromis niloticus; Phytotherapy; Streptococcus agalactiae